Ethanolic Extract of Secang (Caesalpinia sappan L.) Wood Performs as Chemosensitizing Agent Through Apoptotic Induction on Breast Cancer MCF-7 Cells - Khamsita, Rahmi; Hermawan, Adam; Putri, Dyaningtyas Dewi Pamungkas; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2012)
Resistance  to  chemotherapy  is  believed  to  cause  treatment  failure  of  the  patient cancer. Secang (Caesalpinia sappan L.) has been proven to possess anticancer activity on some cancer cell lines. The aimed of this study to develop ethanolic extract of secang wood (EES) as  chemosensitizing  agent  through  apoptotic  induction  on  breast  cancer  MCF-7  cells. Extraction  of  secang  was  done  by  using  maceration  with  70  %  ethanol.  Single  and combinatorial treatment of EES and doxorubicin on MCF-7 breast cancer cells were analyzed by using MTT assay to determine the IC50 value and combination index (CI) to evaluate the combinatorial effect. Apoptosis was analyzed with flowcytometry (annexin V).  EES showed a dose-dependent cytotoxicity (IC50 value of 37 µg/ml), while combinatorial treatment showed that  7  concentrations  was  found  to  be  synergist  with  doxorubicin  on  MCF-7  cells. Combinatorial treatment also triggered apoptotic instead of single treatment. Based on this result,  we  conclude  that  ethanolic  extract  of  secang  wood  is  potential  as  chemosensitizing agent in breast cancer.Keyword: Caesalpinia sappan L, MCF-7 cells, doxorubicin, apoptosis.